2014
DOI: 10.1016/j.jim.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The External Quality Assurance Oversight Laboratory (EQAPOL) proficiency program for IFN-gamma enzyme-linked immunospot (IFN-γ ELISpot) assay

Abstract: The Interferon-gamma Enzyme-Linked ImmunoSpot (IFN-γ ELISpot) assay has been developed and used as an end-point assay in clinical trials for infectious diseases and cancer to detect the magnitude of antigen-specific immune responses. The ability to compare data generated by different laboratories across organizations is pivotal to understand the relative potency of different therapeutic and vaccine strategies. We developed an external proficiency program for the IFN-γ ELISpot assay that evaluates the laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…A weaker IFN-γ formation was associated with better renal function, allowing a milder immunosuppression [23] . Similar to the ImmuKnow ® test, the ELISPOT assay can be standardized and controlled very well [24,25] , which significantly improves the comparability of results between different laboratories. This allows for multicenter studies and increases the chances of routine use if the relevant clinical data are available.…”
Section: Interferon-γ Release From Alloreactive T-cells (Elispot)mentioning
confidence: 99%
“…A weaker IFN-γ formation was associated with better renal function, allowing a milder immunosuppression [23] . Similar to the ImmuKnow ® test, the ELISPOT assay can be standardized and controlled very well [24,25] , which significantly improves the comparability of results between different laboratories. This allows for multicenter studies and increases the chances of routine use if the relevant clinical data are available.…”
Section: Interferon-γ Release From Alloreactive T-cells (Elispot)mentioning
confidence: 99%
“…Eine schwächere IFN-γ Bildung war mit einer besseren Nierenfunktion verbunden und erlaubte eine mildere Immunsuppression [23]. Ähnlich wie der ImmuKnow ® -Test lässt sich der ELISPOT-Test recht gut standardisieren und kontrollieren [24,25], was die Vergleichbarkeit der Ergebnisse zwischen unterschiedlichen Laboratorien enorm verbessert. Das erlaubt multizentrische Studien und vergrößert die Chancen auf einen Routineeinsatz, wenn die entsprechenden klinischen Daten aus Studien vorliegen.…”
Section: Interferon-γ Freisetzung Aus Alloreaktiven T-zellen (Elispot)unclassified
“…The Duke University Human Vaccine Institute (DHVI) has been the central laboratory of the National Institute of Health/National Institute of Allergy and Infectious Diseases (NIH/NIAID) External Quality Assurance Program Oversight Laboratory (EQAPOL) through a Department of Health and Human Services contract since September 2010. As part of this program, EQAPOL has developed and run PT programs for Interferon-gamma (IFN- γ ) Enzyme-linked immunosorbent spot (ELISpot), multiparameter Intracellular Cytokine Staining (ICS) Flow Cytometry and Luminex bead-based multiplex cytokine assays (Lynch et al, 2014; Rountree et al, 2014; Sanchez et al, 2014; Staats et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Both IFN- γ ELISpot and ICS assays, performed to evaluate antigen-specific immune responses, have been subjected to validation procedures (Russell et al, 2003; Horton et al, 2007) according to Good Clinical Laboratory Practice (GCLP) guidelines, and the assays have been performed by EQAPOL laboratories accordingly (Sanchez et al, 2014; Staats et al, 2014). In the germinal paper that compared the performance of the ELISpot assay conducted by several different laboratory sites (Cox et al, 2006; Sanchez et al, 2014), several reagents were found to be key in the overall performance of the assay across laboratories with fetal bovine serum (FBS) being one of them (Cox et al, 2006; Janetzki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation